PROACTIVE COPING, ENGAGEMENT IN LEARNING AND DEEP PROCESSING AS MEDIATORS BETWEEN AUTONOMOUS MOTIVATION AND ADJUSTMENT AT SCHOOL - VIOREL MIH; CODRUȚA MIH; VIOREL DRAGOŞ (Studia Universitatis Babes-Bolyai, 2017)
ABSTRACT. The study explores the role of autonomous motivation in predicting proactive coping, motivational study strategies and tested strategies as mediators of the relationship between coping strategy and adjustment at school. A sample of 183 high school students completed a series of questionnaires assessing motivation, coping, study strategies, and perceptions of adjustment at school. Findings revealed one model for consequences of autonomous motivation. Analyses that used structural equation modeling showed that the students' self‐ determined motivation predicted proactive coping strategy autonomous goal setting with self‐regulatory goal attainment cognitions and behaviour. Further, these resilience resources predicted deep processing, students' intentions to persist in school task, effort, and implicit academic adjustment like education aspiration, homework and students' intentions to persist in high school. The findings underscore the importance of autonomous motivation and proactive coping strategy in adjustment at school and suggest that interventions could usefully target the consequences of these processes. The theoretical and practical implications as well as the controversy over the relation between motivation, coping and school adjustment are discussed.